A new model for multicriteria risk-based tender evaluation - Muner, Wan Farez Saini; Baharom, Fauziah; Yasin, Azman; Mohd, Haslina; Muhd Darus, Norida; Marzuki @ Matt, Zaharin; Muhammad Robie, Mohd Afdhal (American Scientific Publishers, 2014)
Tender evaluation is a critical process for selecting the most appropriate tenderer which potentially increase the probability of IT projects success and ensuring tenderer to deliver the project accordingly.This is in relation to the fact that large IT projects nowadays are founded challenged with several potential risks that lead to poor project progress.Thus, tender evaluation should be evaluated with multi criteria and risk factors to provide more accurate result.This paper discussed the identified multi criteria for tender evaluation. The mapping of standardized multi criteria and risk factors were prepared through content analysis.As a result, there are eight criteria for tender evaluation which includes offered price, contractor credibility, processing time, contractor capability, contractor support service, employee capability, technical solution and document completeness.The risk factors were also defined by determining the risks that might have influence on project success. The risks criteria are user, technology, requirement, project planning and control, project team and organization environment. These mapping of aim to structuring the decision making framework for risk based multicriteria tender evaluation.